DINAMIKA KELOMPOK TANI DI DESA TUNFEU KECAMATAN NEKAMESE KABUPATEN KUPANG - Flavianus Jeharum; Serman Nikolaus; Ida Nurwiana (Buletin Ilmiah Impas, 2023)
This research was conducted in Tunfeu Village, Nekamese District, Kupang Regency from March to April 2021 with the aim of knowing: (1) The level of dynamics of farmer groups in Tunfeu Village, Nekamese District, Kupang Regency which was studied from the aspect of group dynamics elements. (2) The relationship between socio-economic factors of farmer groups (age, education level, experience in farming, land area and number of dependents) with the level of dynamics of farmer groups in Tunfeu Village, Nekamese District, Kupang Regency in farming. The method used in this research is a quantitative approach method. Determination of the location is done purposively. The number of respondents selected was 47, which was taken intentionally from 4 farmer groups in Tunfeu Village. The data collected includes primary data and secondary data. Primary data was obtained through direct interviews with respondents based on a list of questions (Quisoners) that had been prepared in advance; Meanwhile, to obtain secondary data, it is done through searching written documents available in the Agencies and literature related to this research. To find out the first purpose, the data were analyzed using Descriptive Statistical Analysis, namely Group Dynamics Analysis with a Likert Scale approach, while to find out the second purpose the data was analyzed using Spearman's Ladder Correlation. The results of the study are: 1) The dynamics of farmer groups in Tunfeu Village, Nekamese District, Kupang Regency is classified as "Dynam ic" with an average score of 3,39 or (51%). Elements of group pressure and developing and fostering groups that contributed the least amounted to 54%, 57%. 2) Socio-economic factors, namely showing that socio-economic factors such as while age and number of family dependents (tCount<tTable=1,677) do not have a real/significant relationship with farmer group dynamics, education level, farming experience and land area (tCount) >tTable=1,677) has a real/significant relationship with the dynamics of farmer groups in Tunfeu Village, Nekamese District Kupang Regency.